Kemampuan Kognitif Anak Usia Dini Dalam Pembelajaran Akuatik - Lutfi Nur; Anne Hafina; Nandang Rusmana (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2020)
The purpose of this article was to describe the cognitive abilities of early childhood in aquatic learning. This research uses a descriptive method. The subjects in this study were ten students of grade B children aged 5-6 years. The instrument in this study uses structured observation and field notes about children's cognitive ability which include class procedures, pool rules, playing rules, instruction language, and movement mechanics. The data analysis technique used is descriptive statistics. The results showed that the cognitive ability of children aged 5-6 years in the Pilot Laboratory of UPI Campus Tasikmalaya was still in the Start Developing category. This can be seen from the findings in the Tasikmalaya UPI Pilot Laboratory Kindergarten that the score of children's cognitive abilities was 44%.